Lessons from Managing the COVID Pandemic Crisis in Romanian Family Business - Razvan MUSCA; Maria Madela ABRUDAN; Marian NĂSTASE (Revista de Management Comparat International)
The COVID-19 pandemic led to an unprecedented and abrupt crisis that impacted family businesses worldwide and in Romania too. Using the 7S systemic organizational model and the theory of resilience this article focuses on the key concerns and actions taken to mitigate the negative effects of Covid 29 pandemic by the managers of Romanian family firms, some even transforming it in an opportunity for development. The study has identified that Romanian family firms had a rapid reactive approach to the crisis situation, using an informal approach, family based, to analyze the situation, identify the immediate solutions to the lockdown measures, swiftly implementing them by the owner manager of the firm, and begin thinking about innovative solutions for the longer term. Several conclusions and recommendations are provided. By learning from the experiences and strategies shared in this study, family businesses can better prepare for future crises